Why do International Health Regulations self-assessment capacities (SPAR) scores not predict COVID-19 control outcomes? – analysis of the relationship between SPAR scores and COVID-19 resilience scores in 2021 - Fauzi Budi Satria; Feng-Jen Tsai (Globalization and Health)
Abstract Introduction This study analyses the relationship between SPAR and the COVID-19 resilience score (CRS) in 80 countries in 2021 to achieve its objective. Methods We adopted the concept of Bloomberg’s COVID Resilience Ranking to form the CRS, which encompasses three indicators: Reopening Status, COVID Status, and Quality of Life. The average scores of 13 SPAR capacities focused on infectious disease control in 2021 were calculated. Paired t-tests were applied to evaluate the significance of monthly changes in countries’ CRSs. Then, we conducted univariate and multivariate linear regressions to examine the relationship between the SPAR and CRS scores and each CRS indicator. Results The CRS in 80 countries fluctuated throughout 2021. Linear regression revealed a significant relationship between countries’ SPAR scores and CRS (B = 0.03, 95% CI = 0.001, 0.06). Among the CRS indicators, the SPAR was significantly associated with only the Quality of Life indicator (B = 0.01, 95% CI = 0.002, 1.52) and not the Reopening Status and COVID Status indicators. An increase in SPAR score, along with an increase in Governmental Effectiveness, was associated with increased CRS (Adjusted R2 = 0.52, p < 0.05). Moreover, an increase in countries’ SPAR scores was significantly linked to an improvement in people’s Quality of Life (Adjusted R2 = 0.37, p < 0.05). Conclusion The significant relationship between the SPAR and COVID Resilience Scores, particularly the Quality of Life indicator indicates that the lack of accuracy in the ability of the SPAR score to predict COVID-19 control outcomes is attributed to the reliance of the measurement solely on the disease perspective and the limited inclusion of social aspects in the SPAR capacity assessments. Clinical trial number Not Applicable